Remote Facial Expression and Heart Rate Measurements to Assess Human Reactions in Glass Structures - Chiara Bedon; Silvana Mattei (Advances in Civil Engineering)
In engineering applications, human comfort fulfillment is challenging because it depends on several aspects that can be mathematically controlled and optimized, like in case of structural, energy, or thermal issues, and others. Major troubles can indeed derive from combined human reactions, which are related to a multitude of aspects. The so-called “emotional architecture” and its nervous feelings are part of the issue. The interaction of objective and subjective parameters can thus make the “optimal” building design complex. This paper presents a pilot experimental investigation developed remotely to quantify the reactions and nervous states of 10 volunteers exposed to structural glass environments. As known, intrinsic material features (transparency, brittleness, etc.) require specific engineering knowledge for safe mechanical design but can in any case evoke severe subjective feelings for customers, thus affecting their psychological comfort and hence behaviour and movements. This study takes advantage of static/dynamic Virtual Reality (VR) environments and facial expression analyses, with Artificial Intelligence tools that are used to measure both Action Units (AUs) of facial microexpressions and optical heart rate (HR) acquisitions of volunteers exposed to VR scenarios. As shown, within the limits of collected records, the postprocessing analysis of measured signals proves that a rather good correlation can be found for measured AUs, HR data trends, and emotions under various glazing stimuli. Such a remote experimental approach could be thus exploited to support the early design stage of structural glass members and assemblies in buildings.